1993
DOI: 10.1128/mcb.13.11.6919
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C/EBP basic region residues involved in DNA sequence recognition and half-site spacing preference.

Abstract: C/EBP and GCN4 are basic region-leucine zipper (bZIP) DNA-binding proteins that recognize the dyadsymmetric sequences ATTGCGCAAT and ATGAGTCAT, respectively. The sequence specificities of these and other bZIP proteins are determined by their a-helical basic regions, which are related at the primary sequence level. To identify amino acids that are responsible for the different DNA sequence specificities of C/EBP and GCN4, two kinds of hybrid proteins were constructed: GCN4-C/EBP chimeras fused at various positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 88 publications
4
102
0
4
Order By: Relevance
“…Some members of this class of proteins exhibit similar binding speci®cities whereas others are completely di erent. For instance the yeast transcription factor GCN4 recognizes the same target sequence as c-Jun (TGACTCA) whereas c/ EBP binds a target much removed from this sequence (ATTGCGCAAT) (Johnson, 1993;Suckow et al, 1993). Mutational studies have demonstrated that the basic region adjacent to the leucine dimerization domain is directly responsible for speci®city of target recognition in this class of proteins.…”
Section: Construction Of V-jun Mutants With Altered Target Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some members of this class of proteins exhibit similar binding speci®cities whereas others are completely di erent. For instance the yeast transcription factor GCN4 recognizes the same target sequence as c-Jun (TGACTCA) whereas c/ EBP binds a target much removed from this sequence (ATTGCGCAAT) (Johnson, 1993;Suckow et al, 1993). Mutational studies have demonstrated that the basic region adjacent to the leucine dimerization domain is directly responsible for speci®city of target recognition in this class of proteins.…”
Section: Construction Of V-jun Mutants With Altered Target Specificitymentioning
confidence: 99%
“…Mutational studies have demonstrated that the basic region adjacent to the leucine dimerization domain is directly responsible for speci®city of target recognition in this class of proteins. Substitution of a few critical amino acids in the basic region of GCN4 with those found in c/EBP results in a mutant GCN4 protein in which DNA binding speci®city has been altered from TGACTCA (GCN4 target) to ATTGCG-CAAT (c/EBP target) (Johnson, 1993;Suckow et al, 1993). Mutants such as this have the advantage that they exhibit altered functional speci®city while retaining their structural integrity.…”
Section: Construction Of V-jun Mutants With Altered Target Specificitymentioning
confidence: 99%
“…In addition, seven consensus sites that bind the sex-determining region Y transcription factor [36] and its related DNA-binding protein Sox-5 [37] were present throughout the 1.6 kb of Cres promoter sequences. Other DNAbinding sites in the Cres promoter included those for CCAAT\ enhancer-binding protein [38], cAMP-response-element-binding protein [39] and GATA-1-binding protein [40]. Considering the highly restricted expression of the Cres gene to the testicular haploid germ cells, epididymis [20] and the anterior pituitary gonadotropes (G. Sutton and G. A. Cornwall, unpublished work), the presence of some of these DNA-binding elements is not surprising and might suggest a means by which the Cres gene is regulated.…”
Section: Figure 3 Analysis Of the Cres Promoter And 5h Flanking Sequementioning
confidence: 99%
“…S3 F-I). C/EBPα ChIP-chip showed that C/EBPα preferentially binds promoters containing the known C/EBP consensus site (28) and that 85% of bound promoters are unmethylated (Fig. 2E).…”
mentioning
confidence: 99%